2004
DOI: 10.3201/eid1006.030669
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone-resistantCampylobacterInfections: Risk Factors and Clinical Consequences1

Abstract: We integrated data on quinolone and macrolide susceptibility patterns with epidemiologic and typing data from Campylobacter jejuni and C. coli infections in two Danish counties. The mean duration of illness was longer for 86 patients with quinolone-resistant C. jejuni infections (median 13.2 days) than for 381 patients with quinolone-sensitive C. jejuni infections (median 10.3 days, p = 0.001). Foreign travel, eating fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 24 publications
11
145
2
5
Order By: Relevance
“…strains isolated from poultry reveals the impact of the use of these antibiotics in poultry production (ENDTZ et al, 1991;SMITH et al, 1999;ENGBERG et al, 2004;HUMPHREY et al, 2005). Resistance levels vary according to the country, variable factors including the permission to use this drug in poultry production (CHEN et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…strains isolated from poultry reveals the impact of the use of these antibiotics in poultry production (ENDTZ et al, 1991;SMITH et al, 1999;ENGBERG et al, 2004;HUMPHREY et al, 2005). Resistance levels vary according to the country, variable factors including the permission to use this drug in poultry production (CHEN et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The same occurred in the United Kingdom and the United States after the approval of its use in Veterinary Medicine (NACHAMKIN et al, 2002). The acquisition of resistance affects the treatment of patients, increasing the duration of gastrointestinal symptoms in patients infected with resistant strains to fluoroquinolones (SMITH et al, 1999;ENGBERG et al, 2004).…”
Section: Microbiologymentioning
confidence: 99%
“…Moreover, by mechanisms yet to be elucidated, fluoroquinolone resistance appears to coincide with increased fitness of the organism. In humans, fluoroquinolone-resistant strains are shed longer than sensitive isolates (Nelson et al, 2004;Engberg et al, 2004), and they have been reported to out-compete their sensitive counterparts, at least in certain genetic backgrounds, when colonizing poultry, i.e. the natural reservoir of the pathogen (Luo et al, 2005).…”
mentioning
confidence: 99%
“…Engberg et al (2004) reported 2% C. jejuni and 18.5% C. coli strains resistant to erythromycin. Data concerning such a high level of resistance to erythromycin in Campylobacter strains isolated from poultry are surprising having in mind that Denmark is a developed country in which the use of antibiotics is limited to therapeutic indications only.…”
Section: Discussionmentioning
confidence: 99%